2008
DOI: 10.1007/s00449-008-0270-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of pyridine and α-picoline using a strain of the genera Pseudomonas and Nocardia sp.

Abstract: Biodegradation of pyridine and alpha-picoline (2-methyl pyridine) by Pseudomonas pseudoalcaligenes-KPN and Nocardia sp. isolated from garden soil were investigated in batch culture experiments. Pyridine and alpha-picoline (50-200 mg L(-1)) were used as sole source of carbon and energy in the investigation. The kinetic constants were evaluated for pyridine and alpha-picoline degradation under optimized nutritional (C, N, P) and environmental (pH, temperature) conditions. The values of bio-kinetic constant obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
(42 reference statements)
1
5
0
2
Order By: Relevance
“…No inhibition by substrate was observed when the initial pyridine concentration was below 1,212 mg/L. The constant value of Y in non-inhibitory condition was also in agreement with previously reported results (Kumar et al 2005;Singh et al 2008;Padoley et al 2009) that Y was independent of initial substrate concentration below inhibition value. Beyond 1,400 mg/L, a decrease in the values of Y was observed with an increase in pyridine concentration of up to 4,300 mg/L.…”
Section: Kinetic Parameterssupporting
confidence: 92%
See 2 more Smart Citations
“…No inhibition by substrate was observed when the initial pyridine concentration was below 1,212 mg/L. The constant value of Y in non-inhibitory condition was also in agreement with previously reported results (Kumar et al 2005;Singh et al 2008;Padoley et al 2009) that Y was independent of initial substrate concentration below inhibition value. Beyond 1,400 mg/L, a decrease in the values of Y was observed with an increase in pyridine concentration of up to 4,300 mg/L.…”
Section: Kinetic Parameterssupporting
confidence: 92%
“…In the past decades, several species of bacteria capable of degrading pyridine have been isolated and identified. These microorganisms include Pseudomonas (Padoley et al 2009), Gordonia terrea (Stobdan et al 2008), Arthrobacter (Zefirov et al 1994;Gasparavičiūtė et al 2006), Corynebacterium sp. (Shukla and Kaul 1974), Brevibacterium sp.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[15], Gordonia nitida [11,16], Micrococcus luteus [17], Nocardia sp. [2,18], Nocardiodes sp. [9], Paracoccus sp.…”
Section: Introductionmentioning
confidence: 99%
“…[11] and Pseudomonas and Nocardia sp. [13] have been reported to degrade pyridine. Tuo et al [14] reported the degradation of quinoline by Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%